O desenho da cidade e a identidade urbana : o caso da expansão de Cianorte - PR - Dalberto, Anelise Guadagnin (2009)
The present document studies Cianorte's design and urban identity as a planned city in Paraná State. This city was chosen as a case study on account of its project seems different from most of cities in its region, and more, because the project city was implemented divided in two periods, and so, this event resulted in typical differences between the two phases of urban forms of implementation. The Original Plan, made by Jorge Macedo Vieira, shows elements from the English City Garden, resulted from his direct contact with the English city Garden idealizers. But, Cianorte original plan was not completely implemented, due to an economic crisis. So, the areas settled after the 1990 decade had forgotten the existing plan and have grown up following up the farming shared lands. The urban morphology studies detected differences of identity between those two phases. The result has indicated guide lines to equilibrate the identity level in each phase of city's occupation.